2000
DOI: 10.1590/s0037-86822000000500010
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary adiaspiromycosis: report of two cases

Abstract: Two cases of human pulmonary adiaspiromycosis are reported. Patients were 29 and 54-year-old males, farm workers, with "grippe-like" symptoms and radiographic findings suggestive of granulomatous interstitial disease. Transthoracoscopic and transbronchial biopsies were performed. Pulmonary function was measured by spirometry. One patient used ketoconazole. Possibility of misdiagnosed pulmonary adiaspiromycosis is emphasized. Key-words: Pulmonary mycosis. Adiaspiromycosis. Emmonsia parva var crescens. Chrysospo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…Approximately 67 probable cases of human pulmonary adiaspiromycosis due to E. crescens have been described in the literature. England and Hochholzer, in their 1993 case series and review (21), identified 46 cases; there have been 20 other cases reported since that time or that were omitted from the England and Hochholzer review (6,11,13,15,31,32,36,37,38,40,50,51,52,56,60,62) (Table 1). Adiaspiromycosis may be discovered incidentally after histopathologic exam of the lung for other conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 67 probable cases of human pulmonary adiaspiromycosis due to E. crescens have been described in the literature. England and Hochholzer, in their 1993 case series and review (21), identified 46 cases; there have been 20 other cases reported since that time or that were omitted from the England and Hochholzer review (6,11,13,15,31,32,36,37,38,40,50,51,52,56,60,62) (Table 1). Adiaspiromycosis may be discovered incidentally after histopathologic exam of the lung for other conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous cases of adiaspiromycosis have been reported from North America (Guatemala, Honduras, and the United States [Arizona, Georgia, North Carolina, New York, and Oklahoma]), South America (Argentina, Brazil, and Venezuela), and Europe (the former Czechoslovakia, France, Germany, and the former Soviet Union, Spain) (21,53). New countries from which the disease has been reported are Finland and the United Kingdom (13, 40); however, 62% of the 21 new cases from Table 1 were reported from Brazil (11,31,36,37,38,50,51,56). It is unclear if E. crescens is more common in Brazil or if this is simply reporting bias.…”
Section: Frommentioning
confidence: 99%
“…Nos trabalhos existentes, a via inalatória aparece como responsável pela infecção por Emmonsia parva var. crescens [1][2][3][4][5][6][7] . O paciente em questão adquiriu a doença ao inalar os adiásporos junto aos silos, na zona rural, desenvolvendo a forma pulmonar da doença, apesar de ser imunocompetente.…”
Section: Discussionunclassified
“…Essa resolução espontânea constitui a base do conceito atual de ser a adiaspiromicose uma doença autolimitada [2][3][4][5][6][7] . O processo inflamatório alveolar é o eixo central da morbi-mortalidade causada pela adiaspiromicose 4 .…”
Section: Discussionunclassified
See 1 more Smart Citation